Thoracic kidney: a case Report - Rajkumar Rajkumar; Akhilish Maurya; Sunil kumar Singh; Vivek Gupta (International Journal of Medical Research and Review, 2016)
Intrathoracic kidney is rarest type of renal ectopia, which is usually found in males and at left side. Here kidney is situated within the thoracic cavity, not in the pleural space.It occurs due to accelerated ascent of the kidney or delayed closure or maldevelopment of the pleuroperitoneal membrane during intrauterine development of embryo.Intravenous Urography (IVU), ultrasonography, computed tomography (CT) or magnetic resonance imaging (MRI) are performed to confirm the diagnosis. Fortunately patients with this anomaly are generally asymptomatic. A case of 73 year woman is presented here having right thoracic kidney. Patient was having neither symptoms related to renal pathology nor abnormal renal function tests. Slides of Computed tomography study are presented here, which confirmed the diagnosis, with review of literature about intrathoracic kidney.